What Are You, Critical Legal Education? An Absurd Symphony - Luján Pinelo, Aleida; Verdú Sanmartín, Amalia (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This paper challenges the dominance of technology in discussions about transforming the legal profession, which often overlooks crucial debates in legal education, such as curriculum transformation and teaching methodologies. Despite ongoing reforms, mainstream legal education remains largely unchanged, with critical approaches timidly included and to the margins. We question whether current legal education fosters the critical thinking needed to challenge established doctrines. For this, we position critical legal education at the center of the debate, rethinking the idea of "thinking like a lawyer". We explore a co-writing methodology in a dramatic style inspired by the theater of the absurd.